(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
This article raises an important issue of Kazakhstan’s potential to transcend the traditional understanding of Eurasian regionalism, which is mainly associated with the post-Soviet space, including the Eurasian Economic Union. The authors question the broadening of the definition of “Eurasian regionalism” and assess new opportunities for Kazakhstan’s participation in the Eurasian regional process within a broader continental context. Approaching Eurasian regionalism from a new perspective allows us to consider Kazakhstan not only as a participant in the post-Soviet space, but also as a key player at the continental level. The article raises the question of Kazakhstan’s capabilities in the context of Eurasian regionalism, given its geopolitical location and economic potential; the limitations of Kazakhstan’s participation in regional initiatives such as the EAEU and SCO compared to global trends and roles in the region. The article examines the new challenge for Kazakhstan and other Central Asian countries as maintaining independence in the face of changes in the geopolitical environment; the role of international cooperation and integration for Kazakhstan as a strategic element in its foreign policy and economic development. The necessity of diversity of external relations and strategic partnership for Kazakhstan in the conditions of multi-vector approach is emphasized. The article also points out the importance of Kazakhstan’s active participation in international integration processes and its role in global production chains and infrastructure projects to strengthen the economy and increase the country’s status in the global community. Key words: Kazakhstan, multi-vector foreign policy, Eurasian regionalism, EAEU